Analysis hedonic and sensory profile of gayam flour-based velva (Inocarpus fagifer) as a local food product inovation - Nur Setiawati Rahayu; Ahmad Sulaeman; Budi Setiawan; Mokhamad Fakhrudin (AcTion: Aceh Nutrition Journal, 2025)
Velva is a cold and sweet food made from vegetable and fruit puree, in this study the making of velva was modified by using gayam flour to increase the fiber content. Gayam is a local food ingredient that is abundant and has high nutritional and fiber content. This study aimed to determine the sensory attributes that appear and the selected velva products based on panelist assessments. This study was conducted at the IPB Dramaga Campus between June and December 2024. Quantitative Descriptive Analysis (QDA) was used to assess the sensory profile, whereas hedonic testing was conducted using a survey. Panelists for the QDA analysis used trained panelists who had gone through a series of selections; thus, eight trained panelists were obtained for hedonic testing using 35 semi-trained panelists. The results of the QDA test were analyzed descriptively, and the results of the hedonic test were tested using ANOVA. Based on the analysis, the results obtained were significantly different for each sensory attribute of the velva product; the highest difference was in the taste attribute with an F value of 11,22 and a p value of 0,000. Conclusion: Sample A3K2 was a Velva product with the best sensory profile and acceptance by the respondents